A soft chemical route to the synthesis of BiFeO3 nanoparticles with enhanced magnetization. (January 2016) - Hasan, Mehedi; Islam, Md. Fakhrul; Mahbub, Rubayyat; Hossain, Md. Sarowar; Hakim, M.A.
Graphical abstract: Highlights: Pure BiFeO3 nanoparticles have been synthesized at relatively low temperature. Decomposition behavior of BiFeO3 precursor gel is investigated. Particle size dependent magnetic properties have been confirmed. Greatly improved magnetization is observed for BiFeO3 nanostructure. Abstract: Utilization of BiFeO3 (BFO) into modern device applications is restricted by its very low magnetic moments and high leakage current. Enhancement in magnetization is a real challenge for multiferroic BFO in the context of device miniaturization and high density information storage system. In this study a significant improvement in magnetization has been recorded for BFO nanoparticles, exploiting the beneficial effect of size confinement. BFO nanoparticles with different size in the range of 21–68 nm are synthesized via modified Pechini sol–gel approach followed by leaching with acetic acid. X-ray diffraction result confirms pure and well crystallized BFO annealed at temperature lower than 600 °C, compared to more than 800 °C for the traditional solid-state sintering process. A strong size-dependent magnetization which increases with decreasing particle size is confirmed with a value of 1.4 emu/g for 40 nm particles in contrast to 7.5 emu/g for 21 nm particles.